Anti-inflammatory, anti-cholinergic and cytotoxic effects of Sida rhombifolia - Mah, Siau Hui; Teh, Soek Sin; Ee, Gwendoline Cheng Lian (Taylor & Francis, 2017)
CONTEXT: Sida (Malvaceae) has been used as a traditional remedy for the treatment of diarrhoea, malarial, gastrointestinal dysentery, fevers, asthma and inflammation. OBJECTIVES: This study evaluates the anti-inflammatory, cytotoxic and anti-cholinergic activities of Sida rhombifolia Linn. whole plant for the first time. MATERIALS AND METHODS: S. rhombifolia whole plant was extracted by n-hexane, ethyl acetate and methanol using Soxhlet apparatus. The plant extracts were evaluated for their antioxidant (DPPH, FIC and FRAP), anti-inflammatory (NO and protein denaturation inhibitions), cytotoxic (MTT) and anti-cholinesterase (AChE) properties in a range of concentrations to obtain IC50 values. GC-MS analysis was carried out on the n-hexane extract. RESULTS AND DISCUSSION: The ethyl acetate extract exhibited the most significant antioxidant activities by scavenging DPPH radicals and ferrous ions with EC50 of 380.5 and 263.4 μg/mL, respectively. In contrast, the n-hexane extract showed the strongest anti-inflammatory activity with IC50 of 52.16 and 146.03 μg/mL for NO and protein denaturation inhibition assays, respectively. The same extract also revealed the strongest effects in anti-cholinesterase and cytotoxic tests at the concentration of 100 μg/mL, AChE enzyme inhibition was 58.55% and human cancer cells, SNU-1 and Hep G2 inhibition was 68.52% and 47.82%, respectively. The phytochemicals present in the n-hexane extract are palmitic acid, linoleic acid and γ-sitosterol. CONCLUSIONS: The present study revealed that the n-hexane extract possessed relatively high pharmacological activities in anti-inflammation, cytotoxicity and anti-cholinesterase assays. Thus, further work on the detail mechanism of the bioactive phytochemicals which contribute to the biological properties are strongly recommended.